Children's Literature - Olga Maia Fontes (Escola Superior de Educação de Paula Frassinetti, 2009)
The constant concern to keep informed about the best teaching strategies leads us to the examine features related to the later ages but mainly the ones regarding the early ages. Defining Children's Literature has proven to be a difficult and lasting task. Several literary critics and experts have tried to achieve a commonly accepted agreement, even though it has been proven to be quite a hard challenge. This article has the main purposes of pointing out several definitions of Literature (including Children's Literature) and briefly referring to its historical origins.